The effect of transient needle lift on the internal flow and near-nozzle spray characteristics for modern GDI systems investigated by high-speed X-ray imaging. (February 2022) - Mamaikin, Dmitrii; Knorsch, Tobias; Rogler, Philipp; Wang, Jin; Wensing, Michael
The development of the injector nozzle is a dynamic area in regard of several technical aspects. At first, the internal flow influences the near-field spray characteristics via various phenomena such as cavitation and turbulence. However, these phenomena are not fully understood due to their extremely fast, complex and multiscale nature. Furthermore, it governs the spray targeting inside the combustion chamber. High-speed X-ray imaging of GDI injector nozzles is performed in this study. The experimental results presented are related to the internal flow and primary breakup of discharged liquid jets. The injectors used are equipped with nozzles made of aluminum which have been specially developed for these investigations to enhance optical accessibility. The visualization of the needle motion, in-nozzle flow and the primary breakup region provides several exciting observations. First, the needle lift tracking exhibits short overshooting right before the steady-state of the injection phase. This event leads to a short-term, however, significant change in the associated performance of the breakup. This phenomenon is found to be a consequence of the transient behavior of the in-nozzle flow. It is shown that under some circumstances hydraulic flip may occur during this overshooting period. The primary jet breakup region is visualized and evaluated by means of image processing. Thus, the transient behavior of liquid jet expansion is quantified in the vicinity of the nozzle. It is observed that the liquid jet direction deviates from the hole axis already at the nozzle outlet, which is caused by internal flow characteristics.